For a Semiological Exodus: A Way out from the Communication Industry (Disertaciones, 2021)
This article of reflection, which is part of the research project From the Polis to the Politeia. Politics Today, proposes the semiological exodus (a-signifying semiotics) as a resistance to the government of signs of the Mass Media, which following Paolo Virno is called a communicational industry; to sustain this proposal we appeal to the theory of exodus exposed by operaists such as Antonio Negri, Paolo Virno, Michael Hardt and Víctor Moncayo, theory which tends towards flight and escape from the dominant system and not towards the search for state power.
Keywords: Semiological Exodus; Communication Industry; A-significant Semiotics; Semio-capital